If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 = y + -67 Reorder the terms: 8 = -67 + y Solving 8 = -67 + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. 8 + -1y = -67 + y + -1y Combine like terms: y + -1y = 0 8 + -1y = -67 + 0 8 + -1y = -67 Add '-8' to each side of the equation. 8 + -8 + -1y = -67 + -8 Combine like terms: 8 + -8 = 0 0 + -1y = -67 + -8 -1y = -67 + -8 Combine like terms: -67 + -8 = -75 -1y = -75 Divide each side by '-1'. y = 75 Simplifying y = 75
| 1/2m-61=39 | | 4.8x=28.8 | | 6m-5=40+m | | -6x=12n-15 | | 12u-8u=16 | | X+34=11+64 | | 8=y-67/3 | | 6-2=5x-9x+5 | | 9w-5w=20 | | (12-y)+(y+3)=15 | | 0=-.2x^2+10x+5 | | t/5=65 | | 2x/58/10 | | x+1000=9000 | | -3r^2-4r-1=0 | | -7=8+7n-8 | | 2c-c=9 | | 2.3+0.06x=7.1 | | f(x)=-.2x^2+10x+5 | | 10y=6.1927 | | 5x-1(3+2x)=9 | | (x*215.55)+(y*169.48)=188.42 | | 7+34x=17-x | | x+200=1000 | | x+200=100 | | -(x)=33 | | 75-9+7n= | | (2b+1)-(-4)= | | 4f-2=10 | | 0.87p=-3.75 | | 133=2(-8n+-3)+-5 | | 2x-5x+6.3=(-14.4) |